Domestication of the protocol to the African Charter on the rights of women in Africa: the Nigerian religio-cultural perspective - Gambe, Esther (Department of Public Law, 2025)
The Nigerian woman continues to be marginalised both in the private and public spheres despite the nation's ratification of several international and regional instruments on the protection of the rights of women. The Protocol to the African Charter on Human and Peoples Rights on the Rights of Women in Africa (the Maputo Protocol) is one of such instruments. Its domestication in Nigeria is faced with stiff impediments from religious beliefs and cultural practices of the people, women included. This research aims at investigating the religio-cultural practices inhibiting the spirit of the Protocol within the three main cultural groups (Hausa/Fulani, Igbo, and Yoruba) and the three main religious affiliations (African Traditional Religion, Christianity, and Islam) in Nigeria. The thesis concludes by proposing a feasible model that would enable the Protocol to be domesticated in Africa's most populous nation among whom are approximately 101.67 million women and girls. The thesis's argument is that, if properly harnessed, the Protocol can be an effective tool in the realisation of the rights of Nigerian women. This thesis analyses the debate around the universalism and cultural relativism theories, and their effects on the status and rights of women in Nigeria. A review of the status of women during the pre-colonial era is also necessary to rebut the arguments advanced by cultural relativists. Empirically, and using a mix of qualitative and quantitative research methods, questionnaires and face-to-face interviews are conducted with randomly selected women and men from the three main cultural and religious groups under study. The thesis is an emic study that is focused on the perceptions of both Nigerian women and men on the various religious beliefs and cultural norms and practices that negatively impede the rights of women in Nigeria as provided for in the Protocol. The analysis of both the questionnaires and interviews leads to the discovery of perceptions on key indices of the denial of women rights in Nigeria, such as female genital mutilation, widowhood rites and practices, child/forced marriage, and the denial of female inheritance. Furthermore, research findings reveal the ten common factors that propel discrimination against women within the three main religions and cultures in Nigeria: absence of top leadership positions for women; promotion of inequality between husband and wife in marriage; religious silence on cultural specifications on demeaning widows' rites and rituals; discriminatory devolution of property; practice of female genital mutilation/ female circumcision; culture of wife beating; forced sexual intercourse/marital rape; absence of women's right to divorce; and refusal to consider legal options when resolving cases of abuse and violence experienced by women in marriage. In order to develop a proposed model for the domestication of the Protocol within the national values and belief systems in Nigeria, seven key points that would permeate the entire social fabric of the nation, from legal framework and socio-cultural revolution to religious reorientation, are identified and analysed as normative. The research contributes to the discourse on the challenges to the effective domestication of the Protocol within the African continent, Nigeria in particular. It proposes a model for the effective domestication of the Protocol in the face of the contending forces of culture and religion that hold the prima facie evidence of what constitutes the rights of the Nigerian woman. When set in motion, such domestication model will propel the legislative arm of government to review its laws, both at the national, state and local government levels, making them more adaptive to the spirit of the Protocol. More awareness will also be created among women rights activists and women and men at grassroots levels on the possibilities inherent in the Protocol. This would, in turn, propel a joint effort geared towards ensuring the effective protection of the rights of women in Nigeria.